An Optimal Probiotic Carrier: Multiple Steps Toward Selection and Application in Kombucha - Tara Budimac; Lato Pezo; Olja Šovljanski; Dragoljub Cvetković; Teodora Cvanić; Anja Vučetić; Aleksandra Ranitović (Fermentation)
Kombucha is widely recognized as a functional beverage with potential probiotic effects, yet maintaining probiotic viability remains a challenge due to the harsh conditions of fermentation. This study focuses on optimizing probiotic retention by identifying the most effective carrier for Lactobacillus rhamnosus using a multi-criteria decision-making approach. Five carrier materials—pea protein, whey protein, maltodextrin, inulin, and pectin—were assessed through three critical phases: evaluating encapsulated probiotic survival in different pH solutions, examining the impact of carriers on kombucha fermentation, and assessing probiotic stability during storage. The findings indicate that whey protein serves as the most effective carrier, offering superior bacterial protection and enhancing fermentation efficiency. Kinetic modeling further demonstrated a significant correlation between probiotic survival, pH, and titratable acidity, while artificial neural network models achieved high predictive accuracy (r2 > 0.9). Functional analysis revealed that kombucha enriched with probiotic whey protein encapsulates exhibited improved bioactivity, including enhanced antidiabetic properties through α-glucosidase and α-amylase inhibition, antihypertensive effects via ACE inhibition, and antihypercholesterolemic activity through HMGCR inhibition. These findings suggest that probiotic fortification contributes to the beverage’s overall health-promoting potential. Sensory evaluation highlighted that while enriched kombucha exhibited slight modifications in texture and acidity, overall consumer acceptability remained high. The study underscores whey protein’s role as an optimal probiotic carrier, significantly enhancing kombucha’s probiotic stability and bio functional properties. The results contribute to advancements in functional beverage formulation, paving the way for the development of probiotic-enriched kombucha with improved stability, bioactivity, and consumer appeal.